ChatGPT sebagai Tutor Virtual: Dampaknya terhadap Kemampuan Critical Thinking - Bawarta, Westi; Faradika, Faradika; Sari, Intan Utna (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
This study aims to evaluate the impact of using ChatGPT as a virtual tutor on the critical thinking skills of university students in Indonesia. The research is grounded in the growing integration of artificial intelligence technologies in higher education, particularly in self-directed learning processes. A quantitative research method was employed using an experimental survey approach, in which respondents were divided into two groups: an experimental group using ChatGPT as a tutor and a control group using conventional learning methods. Data collection instruments included a critical thinking skills test and a student perception questionnaire. The results revealed a significant improvement in the critical thinking abilities of the experimental group compared to the control group. Students who used ChatGPT demonstrated stronger skills in analyzing arguments, drawing conclusions, and evaluating information objectively. The study concludes that ChatGPT holds potential as an effective learning tool to enhance critical thinking abilities. The implications suggest the wise integration of ChatGPT into higher education systems, while also considering ethical aspects and supervision in its use.